2013
DOI: 10.1186/2050-7445-1-10
|View full text |Cite
|
Sign up to set email alerts
|

The distribution of mercury and other trace elements in the bones of two human individuals from medieval Denmark -- the chemical life history hypothesis

Abstract: Excavating human skeletons is the closest archaeologists can get to the people who lived in the past. Once excavated the bones are often analysed chemically in order to yield as much information as possible. Most archaeometric analyses performed on samples of human skeletal remains have been performed on a single sample from a tooth or a long bone. In this paper we investigate how a suite of elements (Mg, Al, Ca, Mn, Fe, Zn, As, Sr, Ba, Hg and Pb) are distributed in two medieval skeletons excavated at the laym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
49
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(54 citation statements)
references
References 19 publications
5
49
0
Order By: Relevance
“…In the study by Lanocha et al (2012, 2013), bone samples were dried; in our study, bone materials were freeze dried. In comparison, Hg content of the cancellous tissue collected from medieval human bones was up to 40 times higher than that of the cortical tissue (Rasmussen et al 2013). However, the study was carried out only for a very small group (two skeletons).…”
Section: Discussionmentioning
confidence: 97%
“…In the study by Lanocha et al (2012, 2013), bone samples were dried; in our study, bone materials were freeze dried. In comparison, Hg content of the cancellous tissue collected from medieval human bones was up to 40 times higher than that of the cortical tissue (Rasmussen et al 2013). However, the study was carried out only for a very small group (two skeletons).…”
Section: Discussionmentioning
confidence: 97%
“…The Hg concentration in trabecular tissue is generally higher than in compact tissue [50], and the slightly higher values for Hg concentrations in the trabecular tissue for the three individuals USD-252.2, USD-253 [28] and the IntCal13 calibration curve [29].…”
Section: Mercurymentioning
confidence: 99%
“…Schleswig in Germany or Svendborg in Denmark [18]. The likely explanation is that the Al originates from adhered soil [50,[56][57][58] and that Fe is deposited on the bones by the passing groundwater and precipitated by changes in pH [50,[58][59][60]. It is therefore likely that Al and Fe represent two different diagenetic processes.…”
Section: Contamination and Diagenesismentioning
confidence: 99%
See 1 more Smart Citation
“…If someone was treated with mercury for two years from the age of two, and lived to adulthood, little to no mercury would be found. However, if an individual were treated with mercury closer towards the time of death, mercury levels would be detectable, as various studies have shown (Tucker 2007;Rasmussen et al 2008;Rasmussen et al 2013;Zuckerman 2016). Since the excretion of mercury is the issue, it highlights the very importance of dental changes associated with treatments containing mercury and its use when considering the differential diagnosis of congenital syphilis, especially in older individuals.…”
Section: Discussionmentioning
confidence: 98%